The cyclic voltammetric response of electrochemically heterogeneous surfaces - Davies, T; Moore, R; Banks, C; Compton, R (2004)
The cyclic voltammetric response of an electrode composed of two different electrode materials is modelled using finite difference simulations. The system can be thought of as an array of microelectrodes of one material dispersed over a different electrode material. First, a detailed study into the diffusional effects which arise when the distance between the individual microelectrodes is varied, leads to a simple method with which to obtain qualitative data regarding the size of the different electrode materials and diffusion layer thickness. Second, a more quantitative method is employed to determine the fractional coverage and number of gold particles on an anthraquinone modified edge plane pyrolytic graphite electrode by comparing experimental peak to peak separations with simulated working curves. The results are compared with a scanning electron microscope analysis of the same electrode surface. Third, the diffusion domain approach is applied to the basal plane highly ordered pyrolytic graphite (HOPG) surface in an attempt to explain the characteristic shapes of basal plane HOPG voltammograms. A method is presented for the approximate determination of surface defect density, using macroelectrode cyclic voltammetry, and then trialled on a number of different redox couples. The results are compared with two previous scanning tunnelling microscopy studies of basal plane HOPG. © 2004 Elsevier B.V. All rights reserved.